Epileptic spasms are associated with increased stereo‐electroencephalography derived functional connectivity in tuberous sclerosis complex. Issue 9 (25th July 2022) - Neal, Andrew; Bouet, Romain; Lagarde, Stanislas; Ostrowsky‐Coste, Karine; Maillard, Louis; Kahane, Philippe; Touraine, Renaud; Catenoix, Helene; Montavont, Alexandra; Isnard, Jean; Arzimanoglou, Alexis; Hermier, Marc; et al.
Abstract: Objective: Epileptic spasms (ES) are common in tuberous sclerosis complex (TSC). However, the underlying network alterations and relationship with epileptogenic tubers are poorly understood. We examined interictal functional connectivity (FC) using stereo‐electroencephalography (SEEG) in patients with TSC to investigate the relationship between tubers, epileptogenicity, and ES. Methods: We analyzed 18 patients with TSC who underwent SEEG (mean age = 11.5 years). The dominant tuber (DT) was defined as the most epileptogenic tuber using the epileptogenicity index. Epileptogenic zone (EZ) organization was quantitatively separated into focal (isolated DT) and complex (all other patterns). Using a 20‐min interictal recording, FC was estimated with nonlinear regression, h 2 . We calculated (1) intrazone FC within all sampled tubers and normal‐appearing cortical zones, respectively; and (2) interzone FC involving connections between DT, other tubers, and normal cortex. The relationship between FC and (1) presence of ES as a current seizure type at the time of SEEG, (2) EZ organization, and (3) epileptogenicity was analyzed using a mixed generalized linear model. Spike rate and distance between zones were considered in the model as covariates. Results: Six patients had ES as a current seizure type at time of SEEG. ES patients had a greater number of tubers with a fluid‐attenuated inversion recovery hypointense center ( p < .001), and none had TSC1 mutations. The presence of ES was independently associated with increased FC within both intrazone ( p = .033) and interzone ( p = .011) networks. Post hoc analyses identified that increased FC was associated with ES across tuber and nontuber networks. EZ organization and epileptogenicity biomarkers were not associated with FC. Significance: Increased cortical synchrony among both tuber and nontuber networks is characteristic of patients with ES and independent of both EZ organization and tuber epileptogenicity. This further supports the prospect of FC biomarkers aiding treatment paradigms in TSC.